Coeliac disease and risk of sepsis. Issue 8 (12th February 2008) - Ludvigsson, J F; Olén, O; Bell, M; Ekbom, A; Montgomery, S M
Abstract : Objective: To examine the risk of subsequent sepsis in individuals with coeliac disease. Design: We used Swedish national health registers to identify 15 325 individuals with a diagnosis of coeliac disease (1964–2003) and 14 494 inpatient reference individuals. Cox regression estimated the hazard ratios (HRs) for subsequent sepsis. Results: Compared with inpatient reference individuals, individuals with coeliac disease were at increased risk of sepsis (HR  = 1.6, 95% confidence interval (95% CI)  = 1.2 to 1.9, p<0.001). The highest risk estimates were seen for pneumococcal sepsis (HR  = 2.5, 95% CI  = 1.2 to 5.1, p = 0.014). Individuals with coeliac disease diagnosed in childhood were not at increased risk of subsequent sepsis (HR  = 1.0, 95% CI  = 0.6 to 1.9, p = 0.908). When individuals with coeliac disease were compared with reference individuals from the general population, coeliac disease was associated with an increased risk of sepsis (HR  = 2.6, 95% CI  = 2.1 to 3.0, p<0.001). The HR for pneumococcal sepsis was 3.9 (95% CI  = 2.2 to 7.0, p<0.001). In this comparison, children with coeliac disease were also at an increased risk of sepsis (HR  = 1.8, 95% CI  = 1.2 to 2.7, p = 0.003). Conclusion: This study showed a modestly increased risk of sepsis in patients with coeliac disease with the highest risk for pneumococcal sepsis. This risk increase was limited to those with coeliac disease diagnosed in adulthood. Potential explanations include hyposplenism, increased mucosal permeability and an altered composition of the intestinal glycocalyx in individuals with coeliac disease.